Anthropology of Economic Thought (Economics of the ancient world as a model) - Mansoor, Ahmad I. A.; Haji, Bawer A. (Academic Journal of Nawroz University, 2020)
Economic anthropologists had no choice but to note that the world around them is changing rapidly; in the form of cases that vary from one society to another in ethics, technology, and production relationships. We know that the most sophisticated links were the result of the mechanical revolution or the so-called industrial revolution, but the question that occupied them was how it was Primitive man lives his life without this development? And that most of the anthropologists with a central intellectual mindset in Europe began their studies in the countries of the Greeks assuming that the real economic life began with them, and they marveled that how the simple Greek man was responsible for securing the needs of his house! But some other anthropologists went further, that is, by studying the economic ideas in Mesopotamia, the cradle of civilizations, and they assumed that the movement of society is a continuous evolutionary movement in different situations, and that the Greek economy is a link in the evolutionary chain, before there was an economy dependent on slaves in a country The Greeks, there was an economy dependent on hunting and then on agriculture and livestock to trade and exchange of goods as they were in Sumer, Babylon, Egypt, Assyria and others.